Aberrant immunoglobulin synthesis in light chain amyloidosis. Free light chain and light chain fragment production by human bone marrow cells in short-term tissue culture. - Buxbaum, J (The Journal of Clinical Investigation, 1986)
Bone marrow cells obtained from 14 patients with light chain amyloid (AL) deposition were examined by biosynthetic labeling techniques. These analyses identified free monoclonal light chain (L-chain) synthesis even in those patients whose serum or urine contained no M protein or free L-chains or only an intact M protein. The experiments also identified a subset of patients whose plasma cells synthesized polypeptides bearing constant region antigenic determinants that migrated more rapidly than intact L-chains on polyacrylamide gels. Since most AL fibrils contain L-chain fragments rather than intact L-chains, these studies suggested that the genesis of the fibril components may reflect aberrant synthesis, proteolytic processing, or both. We also noted that in some individuals the pattern of Ig synthesis normalized after several courses of cytotoxic therapy. Thus, we could use bone marrow Ig synthesis as a sensitive biochemical parameter for monitoring therapy. Finally, the presence of aberrant synthetic products in these clones raised questions about their origin with respect to the normal processes of transcription, translation, and posttranslational modification in Ig-producing cells. Images